ChemInform Abstract: (2‐Chlorobenzoyloxy)copper(I) Catalyzed C—S Cross‐Coupling of Di(hetero)aryl Disulfides with Aryl Boronic Acids under Base‐Free Conditions. Issue 41 (October 2015) - Guo, Yan; Quan, Zheng‐Jun; Da, Yu‐Xia; Zhang, Zhang; Wang, Xi‐Cun
Abstract Arylboronic acids with strong electron‐withdrawing groups (e.g., 4‐CHO, 4‐Ac or 4‐COOH) do not react with compound (I) and also diallyl and di‐tert‐butyl disulfides fail in the reaction with (IIa).